A misfolded dimer of Cu/Zn‐superoxide dismutase leading to pathological oligomerization in amyotrophic lateral sclerosis. (12th February 2017) - Anzai, Itsuki; Tokuda, Eiichi; Mukaiyama, Atsushi; Akiyama, Shuji; Endo, Fumito; Yamanaka, Koji; Misawa, Hidemi; Furukawa, Yoshiaki
Abstract: Misfolding of mutant Cu/Zn‐superoxide dismutase (SOD1) is a pathological hallmark in a familial form of amyotrophic lateral sclerosis. Pathogenic mutations have been proposed to monomerize SOD1 normally adopting a homodimeric configuration and then trigger abnormal oligomerization of SOD1 proteins. Despite this, a misfolded conformation of SOD1 leading to the oligomerization at physiological conditions still remains ambiguous. Here, we show that, around the body temperature (∼37°C), mutant SOD1 maintains a dimeric configuration but lacks most of its secondary structures. Also, such an abnormal SOD1 dimer with significant structural disorder was prone to irreversibly forming the oligomers crosslinked via disulfide bonds. The disulfide‐crosslinked oligomers of SOD1 were detected in the spinal cords of the diseased mice expressing mutant SOD1. We hence propose an alternative pathway of mutant SOD1 misfolding that is responsible for oligomerization in the pathologies of the disease.